Tools for the discovery of biopolymer producing cysteine relays - Mabbitt, Peter D. (Biophys Rev, 2021)
Cysteine relays, where a protein or small molecule is transferred multiple times via transthiolation, are central to the production of biological polymers. Enzymes that utilise relay mechanisms display broad substrate specificity and are readily engineered to produce new polymers. In this review, I discuss recent advances in the discovery, engineering and biophysical characterisation of cysteine relays. I will focus on eukaryotic ubiquitin (Ub) cascades and prokaryotic polyhydroxyalkanoate (PHA) synthesis. These evolutionarily distinct processes employ similar chemistry and are readily modified for biotechnological applications. Both processes have been studied intensively for decades, yet recent studies suggest we do not fully understand their mechanistic diversity or plasticity. I will discuss the important role that activity-based probes (ABPs) and other chemical tools have had in identifying and delineating Ub cysteine-relays and the potential for ABPs to be applied to PHA synthases. Finally, I will offer a personal perspective on the potential of engineering cysteine-relays for non-native polymer production.